Product-focused software process improvement 12th international conference, PROFES 2011, Torre Canne, Italy, June 20-22, 2011 : proceedings - Caivano, Danilo (Lecture notes in computer science, 2011)
This book constitutes the refereed proceedings of the 12 International Conference on Product-Focused Software Process Improvement, PROFES 2011, held in Torre Canne, Italy, in June 2011. The 24 revised full papers presented together with the abstracts of 2 keynote addresses were carefully reviewed and selected from 54 submissions. The papers are organized in topical sections on agile and lean practices, cross-model quality improvement, global and competitive software development, managing diversity, product and process measurements, product-focused software process improvement, requirement process improvement, and software process improvement.